COMPARATIVE STUDY OF SAFETY AND EFFICACY OF DESVENLAFLEXINE VERSUS SERTRALINE : A RANDOMISED CONTROL TRIAL - A.P.SINGH; MOHIT TRIVEDI; DEVENDRA SINGH KUSHWAH (International Journal of Pharma and Bio Sciences, 2014)
Desvenlaflexine (SNRI) and Sertraline (SSRI) were compared to evaluate the safety in mild to moderate depressive disorder. A 6 Inter departmental work between psychiatry and pharmaology was carried out in, ajkiya Medical College Ambedkarnagar (U.P) and N.SCB Medical College Jabalpur,(M.P) (n= 60 patients) on patients suffering from depression single episode (5 F 32.0 or 5F 32.1 A/T ICD X), recurrent depressive disorder (5 F 33.0 or 5F 33.1 A/T ICD X) was conducted. Scoring on MADRS was kept as primary end point. Subjects were randomly assigned (1:1) into two different groups (Desvenlaflexine 50-100 mg/day (flexibly dosed) and to sertraline 50-1000mg/day) i.e. Group A and Group B with the step-up dosing pattern. Change in score of MADRS was main determinant of the study during its tenure and a greater proportion of sertraline-treated patients completed the 6-week study compared with desvenlaflexine - treated patients. At week 6, Desvenlaflexine treatment resulted in slightly lesser improvement, more drop outs, and more adverse effects compared with sertraline, however the differences were not clinically significant. These findings suggest that SSRI, Sertraliune is better tolerated and at least as effective as the SNRI, Desvenlaflexine in the treatment of major depressive disorder with mild to moderate severity.